Teacher Professional Competence of Volunteer Quranic Tutors in Increasing the Interest in Quranic Learning Among School Dropouts at Rumah Tahsin Ar-Rahman, Samarinda: Kompetensi Profesionalisme Guru Pada Relawan Pengajar Mengaji Gratis Dalam Meningkatkan Minat Belajar Mengaji Anak Putus Sekolah Di Rumah Tahsin Ar-Rahman Kota Samarinda - Salim, Rio Gunawan; Dadang Yunus Lutfiansyah; Viena Rusmiati Hasanah; Karina Farmawati, Windie (Borneo Educational Journal (Borju), 2026)
This study aims to analyze the professional competence of volunteer teachers who provide free Quran recitation lessons in increasing the interest in learning among out-of-school children at Rumah Tahsin Ar-Rahman, Samarinda City. This tahsin house is a community self-help initiative of the Cahaya Kreatif Sinergi Foundation and the Samarinda City Women's Empowerment and Child Protection Agency (DP2PA) to facilitate non-formal religious education for socially vulnerable groups in order to respond to the social problem of assisting school dropouts due to family economic constraints. Although the teachers are volunteers without formal teaching backgrounds or teaching certifications, they are required to have adaptive pedagogical strategies. This study uses a qualitative approach with a case study design. Data were collected through participatory observation, semi-structured interviews with foundation administrators, volunteer teachers, and students (focusing on school dropouts), as well as documentation. Data analysis applied the interactive model of Miles and Huberman. The results showed that the professional competence of volunteer Quran teachers played an important role in increasing the interest in learning the Quran among school dropouts, as seen from the volunteers' ability to apply professional competencies in practice. These competencies are dominated by strengths in the affective-motivational dimension (sincerity, motivation, and emotional regulation), which are supported by the cognitive dimension (mastery of tajwid material), the pedagogical dimension (varied and interactive methods), and the interpersonal dimension (empathic communication), thereby increasing the interest in learning among school dropouts, as indicated by improved focus (attention), understanding of religious values (relevance), self-confidence (confidence), and enthusiasm for learning (satisfaction). This study provides empirical evidence that in the non-formal religious education ecosystem, the absence of certification and academic qualifications in teaching can be effectively bridged by high affective-motivational competence and a humanistic approach by educators.